The Role of Spatial Heterogeneity in Sexual Selection and the Evolution of Exaggerated Animal Weapons - Wilson, Audrey (My University, 2021)
Sexually selected male weaponry are among the most diverse and elaborate traits seen in the animal kingdom and often aid males in securing resources and mates, providing a fitness advantage to those that bear them. Yet, while intra-sexual competition between males to secure mates is common, weaponry is a rare trait that is observed in few taxa. Building upon previous theory, Emlen predicted that exaggerated animal weaponry evolves when, (i) there is intense competition between males for access to females, (ii) the biology or behaviour of a species generates high variance in male reproductive success, and (iii) competitions between males promote extreme weapon size evolution. While there are many species bearing weaponry that appear to fit these contexts, it has yet to be tested if these conditions are sufficient to initiate the evolution of exaggerated weaponry. For my research, I created three environmental treatments that emulated the three conditions proposed by Emlen. Using these treatments, I conducted experiments using Drosophila melanogaster to examine the effects of spatial structure on natural and sexual selection with a focus on the initial stages of the evolution of exaggerated trait weaponry that arise from this process. From these experiments, I found that the strength of sexual and other components of natural selection vary with environmental complexity and mutational effect. I also found that these environmental treatments generate weak differences in condition dependence and allometry of fly morphological traits that could be indicative of early weapon evolution. With these experiments, I provide the initial framework to test whether the conditions proposed by Emlen are both necessary and sufficient to lead to the initial evolution of exaggerated animal weaponry and demonstrate that these conditions may indeed create the circumstances that allows this evolution to occur.
Keywords: Evolution; Sexual Selection; Animal Weaponry; Drosophila